Empirical Evidence on the Acceleration Principle: A Comment - Hines, A. G. (Review of Economic Studies, 1968)
Journal Article Empirical Evidence on the Acceleration Principle: A Comment Get access A. G. Hines A. G. Hines University College, London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 3, July 1968, Pages 347–349, https://doi.org/10.2307/2296667 Published: 01 July 1968